(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The rapid increase in the proportion of sexually active adolescents is exposing large numbers of youths to the risk of unwanted pregnancies and sexually transmitted diseases including HIV/AIDS. Promotion and strengthening of reproductive health education and services, especially among adolescents requires access to current baseline data on knowledge, attitude and practice of contraception among adolescents, including secondary school students. This data is very scanty for Tanzania. The aim of this work was to determine the knowledge, attitude and practice of contraceptive use among secondary school students in the Dar es Salaam region of Tanzania. Ilala district of Dar es salaam has a high concentration of secondary schools enrolling a cosmopolitan population of students hailing from most regions of the country. These come from various social-economic backgrounds effectively representing the general Tanzanian population. The study was designed as a cross-sectional descriptive study. Secondary school students aged 14 to 19 years were interviewed on their knowledge, attitude and practice on contraceptive use using a structured questionnaire. A total of 200 students (126 females, 74 males) participated in the study. Knowledge on contraceptive use was found to be good to average (75%). Knowledge and prevalence of contraceptive use was found to increase with age, current use and positive attitude. Female students had better knowledge on contraception than male students. Good knowledge on contraception did not translate into increased use, the prevalence of use being only 34% as compared to 75% of students with average to good knowledge. More students reported using the male condom for contraception. Most students (69.5%) mentioned pharmacies and drug stores as their main source of contraceptives. These findings underscore the need for early education on human sexuality and the benefits of family planning. Health care providers, including pharmacists, must be trained to be able to provide adequate basic contraceptive services to adolescents and the general public. There is need to improve access to contraceptive services by adolescents.